Catatonia and melancholia interface: exploring a new paradigm for evaluation and treatment. A case series and literature review - Mahgoub, Yassir; Pathare, Aum; Hamlin, Dallas; Gomaa, Hassaan; Nutting, Sean; Mormando, Charles; Francis, Andrew (Frontiers in Psychiatry, 2024)
Background: Catatonia has been increasingly associated with mood disorders and is recognized as a specifier in the DSM-5 and DSM-5-TR (Abrams & Taylor, 1976) (APA, 2013) (APA, 2022). The DSM-5-TR recognizes melancholia as a specifier for depressive episodes in major depressive disorder and bipolar disorder. It is characterized by severe anhedonia, lack of reactivity, excessive or delusional guilt, and significant vegetative symptoms (APA, 2022). As the conceptualization of melancholia expanded beyond its mood components to include psychomotor disturbances, its overlap with psychomotor symptoms or catatonia becomes evident (Taylor & Fink, 2008). This overlap was also described in Kahlbaum’s original literature, where he describes the transition between states of melancholia, mania, and catatonia (Kahlbaum, 1874). Method: Case summary of six patients with major depressive disorder or depressed phase of bipolar disorder who were admitted for severe depression, anhedonia, intense anxiety, psychomotor agitation or retardation, indecisiveness, perseveration, and vegetative symptoms such as poor sleep, appetite, and significant weight loss. Results: All patients demonstrated rapid and complete resolution of their mood and psychomotor symptoms, indecisiveness, perseveration, as well as psychosis shortly after administration of lorazepam, with recurrence of the above symptoms upon lorazepam discontinuation and resolution upon resumption, in an on-and-off manner. Conclusion: The present study argues for a closer relationship between melancholia and catatonia based on our case series, historical review, overlap in phenomenology, and response to treatment. We propose preliminary [Mahgoub] criteria for patients with severe depression and melancholia. The role of GABA agonists, such as lorazepam, can be explored as an option for patients with treatment-resistant depression who meet these criteria for melancholia. Limitations: Absence of a standardized, systematic assessment tool and a small sample size.